Exploratory Data Analysis Pada Dataset Ulasan Pelanggan Mc’Donald di Australia - William Wijaya (Journal of Smart Technology and Engineering, 2025)
Abstract — This research, titled “Analysis of Customer Reviews of McDonald's in Australia” aims to enhance service quality, which is a crucial aspect for fast-food restaurants in maintaining customer satisfaction. This study analyzes McDonald's customer reviews in Australia to identify key factors influencing customer experience. The data used comes from the McDonald's customer review dataset available on Kaggle. The methods employed include sentiment analysis based on Natural Language Processing (NLP) and exploratory data analysis techniques to identify common trends in the reviews. The results indicate that factors such as food quality, service speed, restaurant cleanliness, and staff interaction significantly impact customer sentiment. These findings can serve as a foundation for McDonald's to improve underperforming service aspects while reinforcing elements that have received positive customer feedback. By leveraging NLP-based data analysis, restaurants can better understand customer preferences and enhance their service strategies to boost customer loyalty.